Penguatan demokrasi indonesia melalui aktualisasi nilai-nilai pancasila - Aziz, Afif Ramdlani (Maliki Interdisciplinary Journal, 2025)
Democracy in Indonesia continuously faces challenges, ranging from political polarization, vote buying practices, to weak substantive public participation. Meanwhile, the foundational values of the state, Pancasila namely Belief in One Supreme God, Just and Civilized Humanity, The Unity of Indonesia, Democracy Guided by the Inner Wisdom of Deliberations/Representations, and Social Justice for All Indonesians have significant potential to serve as moral, ethical, and practical bases for strengthening Indonesia’s democratic system. This article aims to examine how the actualization of Pancasila values can strengthen Indonesian democracy through a qualitative narrative approach based on literature review. Findings show that consistent implementation of Pancasila values in civic education, political ethics, democratic institutions, and citizen participation can enhance the quality of democracy that is inclusive, participatory, and socially just. Recommendations include revitalizing character education, reforming democratic institutions, and applying value-based digital literacy.